Korelasi Panjang Tulang Tibia Terhadap Tinggi Badan Pada Mahasiswa FK UMSU - Putra Diandro Utama Ritonga; Hendra Sutysna (Smart Medical Journal, 2018)
Introduction: Estimation of body height is one of the important parameter in the anthropology forensic, which the body height became the first action in identification. The regression formula using the tibia length, sex, and age might have valid approximation for body height which helpful in clinical context. Methods: The analytic descriptive researchwith the cross-sectional design was done on 112 subject consist of male and female satisfy inclusion and exclusion criteria. Sample was selected by total sampling technique.Results: Tibia length resulting correlation ranging between 0,488 and 0,968 (p<0,001). The linear regression formula showed Standard Error of the Estimate (SEE) ranging between 0,810 and 3,495 (p<0,001). Conclusion: A significant correlation between tibia length and body heightwas found with a strong correlation. Hence, a linear regression formula was derived for the estimation of body height from tibia length.Keywords: tibia length; body height; regression formula; anthropometry